A Note on Some Strongly Sequence Spaces - Ekrem Savaş; Adem Kılıçman (Abstract and Applied Analysis, 2011)
We introduce and study new sequence spaces which arise from the notions of generalized de la Vallée-Poussin means, invariant means, and modulus functions.